A proteomic study of Clavibacter michiganensis subsp. michiganensis culture supernatants. - Hiery, Eva; Poetsch, Ansgar; Moosbauer, Tanja; Amin, Bushra; Hofmann, Jörg; Burkovski, Andreas (Proteomes, 2015)

Human promyelocytic leukemia protein is targeted to distinct subnuclear domains in plant nuclei and colocalizes with nucleolar constituents in a SUMO-dependent manner - Lamm, Christian; Scherer, Myriam; Reuter, Nina; Amin, Bushra; Stamminger, Thomas; Sonnewald, Uwe (FEBS Open Bio, 2016)
Eukaryotic nuclei are subdivided into subnuclear structures. Among the most prominent of these structures are the nucleolus and the PML nuclear bodies (PML-NBs). PML-NBs are spherical multiprotein aggregates of varying size localized in the interchromosomal area. PML-NB formation is dependent on the presence of the promyelocytic leukemia protein (PML) as well as on post-translational modification of core components by covalent attachment of the small ubiquitin-like modifier (SUMO). So far, PML-NBs as well as PML have been described in mammalian cells only, whereas no orthologs are known in the plant kingdom. In order to investigate conserved mechanisms in PML targeting, we expressed human PML (hPML) fused to the GFP in Nicotiana benthamiana. Using confocal laser scanning microscopy and coimmunoprecipitation followed by mass spectrometric analysis, we found the fusion protein in association with nucleolar constituents. Importantly, mutants of hPML, which are no longer SUMOylated, showed altered localizations, implying SUMO-dependent targeting of hPML in plants as has previously been shown for mammalian cells. Interestingly, in the presence of proteasome inhibitors, hPML could also be found in the nucleolus of mammalian cells suggesting conserved targeting mechanisms of PML across kingdoms. Finally, Solanum tuberosum COP1, a proposed PML-like protein from plants, was fused to the red fluorescent protein (RFP) and coexpressed with hPML::eGFP. Microscopic analysis confirmed the localization of COP1::RFP in nuclear speckles. However, hPML::eGFP did not colocalize with COP1::RFP. Hence, we conclude that plants do not possess specialized PML-NBs, but that their functions may be covered by other subnuclear structures like the nucleolus.
Keywords: nucleolus; plant subnuclear structures; promyelocytic leukemia protein; nuclear bodies; small ubiquitin like modifier

Macrophage phosphoproteome analysis reveals MINCLE-dependent and-independent mycobacterial cord factor signaling - Hansen, Madlen; Peltier, Julian; Killy, Barbara; Amin, Bushra; Bodendorfer, Barbara; HäRtlova, Anetta; Uebel, Sebastian; Bosmann, Markus; Hofmann, Jörg; Büttner, Christian; Ekici, Arif Bülent; Kuttke, Mario; et al. (Molecular & Cellular Proteomics, 2019)
Immune sensing of Mycobacterium tuberculosis relies on recognition by macrophages. Mycobacterial cord factor, trehalose-6,6-dimycolate (TDM), is the most abundant cell wall glycolipid and binds to the C-type lectin receptor (CLR) MINCLE. To explore the kinase signaling linking the TDM-MINCLE interaction to gene expression, we employed quantitative phosphoproteome analysis. TDM caused upregulation of 6.7% and suppressed 3.8% of the 14,000 phospho-sites identified on 3727 proteins. MINCLE-dependent phosphorylation was observed for canonical players of CLR signaling (e.g. PLC, PKC), and was enriched for PKC and GSK3 kinase motifs. MINCLE-dependent activation of the PI3K-AKT-GSK3 pathway contributed to inflammatory gene expression and required the PI3K regulatory subunit p85. Unexpectedly, a substantial fraction of TDM-induced phosphorylation was MINCLE-independent, a finding paralleled by transcriptome data. Bioinformatics analysis of both data sets concurred in the requirement for MINCLE for innate immune response pathways and processes. In contrast, MINCLE-independent phosphorylation and transcriptome responses were linked to cell cycle regulation. Collectively, our global analyses show substantial reprogramming of macrophages by TDM and reveal a dichotomy of MINCLE-dependent and-independent signaling linked to distinct biological responses.
CRIS-Team Scopus Importer:2019-05-02

Nuclear trafficking of the anti-apoptotic Coxiella burnetii effector protein AnkG requires binding to p32 and Importin-alpha 1 - Schäfer, Walter; Eckart, Rita; Schmid, Benedikt; Cagkoeylue, Hasret; Hof, Kerstin; Muller, Yves; Amin, Bushra; Lührmann, Anja (Cellular Microbiology, 2017)
The obligate intracellular bacterium Coxiella burnetii causes the zoonotic disease Q-fever. Coxiella pathogenesis depends on a functional type IV secretion system (T4SS). The T4SS effector AnkG inhibits pathogen-induced host cell apoptosis, which is believed to be important for the establishment of a persistent infection. However, the mode of action of AnkG is not fully understood. We have previously demonstrated that binding of AnkG to p32 is crucial for migration of AnkG into the nucleus and that nuclear localization of AnkG is essential for its antiapoptotic activity. Here, we compared the activity of AnkG from the C. burnetii strains Nine Mile and Dugway. Although there is only a single amino acid exchange at residue 11, we observed a difference in anti-apoptotic activity and nuclear migration. Mutation of amino acid 11 to glutamic acid, threonine or valine results in AnkG mutants that had lost the anti-apoptotic activity and the ability to migrate into the nucleus. We identified Importin-a1 to bind to AnkG, but not to the mutants and concluded that binding of AnkG to p32 and Importin-a1 is essential for migration into the nucleus. Also during Coxiella infection binding of AnkG to p32 and Importin-a1 is crucial for nuclear localization of AnkG.
EVALuna2:7733

Nuclear trafficking of the anti-apoptotic Coxiella burnetii effector protein AnkG requires binding to p32 and Importin-α1 - Schäfer, Walter; Eckart, Rita; Schmid, Benedikt; Cagköylü, Hasret; Hof, Kerstin; Muller, Yves; Amin, Bushra; Lührmann, Anja (Cellular Microbiology, 2016)
The obligate intracellular bacterium Coxiella burnetii causes the zoonotic disease Q-fever. Coxiella pathogenesis depends on a functional type IV secretion system (T4SS). The T4SS effector AnkG inhibits pathogen-induced host cell apoptosis, which is believed to be important for the establishment of a persistent infection. However, the mode of action of AnkG is not fully understood. We have previously demonstrated that binding of AnkG to p32 is crucial for migration of AnkG into the nucleus and that nuclear localization of AnkG is essential for its anti-apoptotic activity. Here, we compared the activity of AnkG from the C. burnetii strains Nine Mile and Dugway. Although there is only a single amino acid exchange at residue 11, we observed a difference in anti-apoptotic activity and nuclear migration. Mutation of amino acid 11 to glutamic acid, threonine or valine results in AnkG mutants that had lost the anti-apoptotic activity and the ability to migrate into the nucleus. We identified Importin-α1 to bind to AnkG, but not to the mutants and concluded that binding of AnkG to p32 and Importin-α1 is essential for migration into the nucleus. Also during Coxiella infection binding of AnkG to p32 and Importin-α1 is crucial for nuclear localization of AnkG.
EVALuna2:7709

Protein kinases responsible for the phosphorylation of the nuclear egress core complex of human cytomegalovirus - Sonntag, Eric; Milbradt, Jens; Svrlanska, Adriana; Strojan, Hanife; Haege, Sigrun; Kraut, Alexandra; Hesse, Anne-Marie; Amin, Bushra; Sonnewald, Uwe; Coute, Yohann; Marschall, Manfred (Journal of General Virology, 2017)
Nuclear egress of herpesvirus capsids is mediated by a multi-component nuclear egress complex (NEC) assembled by a heterodimer of two essential viral core egress proteins. In the case of human cytomegalovirus (HCMV), this core NEC is defined by the interaction between the membrane-anchored pUL50 and its nuclear cofactor, pUL53. NEC protein phosphorylation is considered to be an important regulatory step, so this study focused on the respective role of viral and cellular protein kinases. Multiply phosphorylated pUL50 varieties were detected by Western blot and Phos-tag analyses as resulting from both viral and cellular kinase activities. In vitro kinase analyses demonstrated that pUL50 is a substrate of both PKC alpha and CDK1, while pUL53 can also be moderately phosphorylated by CDK1. The use of kinase inhibitors further illustrated the importance of distinct kinases for core NEC phosphorylation. Importantly, mass spectrometry-based proteomic analyses identified five major and nine minor sites of pUL50 phosphorylation. The functional relevance of core NEC phosphorylation was confirmed by various experimental settings, including kinase knock-down/knock-out and confocal imaging, in which it was found that (i) HCMV core NEC proteins are not phosphorylated solely by viral pUL97, but also by cellular kinases; (ii) both PKC and CDK1 phosphorylation are detectable for pUL50; (iii) no impact of PKC phosphorylation on NEC functionality has been identified so far; (iv) nonetheless, CDK1-specific phosphorylation appears to be required for functional core NEC interaction. In summary, our findings provide the first evidence that the HCMV core NEC is phosphorylated by cellular kinases, and that the complex pattern of NEC phosphorylation has functional relevance.
Keywords: human cytomegalovirus; nuclear egress; core NEC; protein-protein interaction; cellular protein kinases; phosphorylation

Proteomic interaction patterns between human cyclins, the cyclin-dependent kinase ortholog pUL97 and additional cytomegalovirus proteins - Steingruber, Mirjam; Kraut, Alexandra; Socher, Eileen; Sticht, Heinrich; Reichel, Anna; Stamminger, Thomas; Amin, Bushra; Coute, Yohann; Hutterer, Corina; Marschall, Manfred (Viruses, 2016)
The human cytomegalovirus (HCMV)-encoded cyclin-dependent kinase (CDK) ortholog pUL97 associates with human cyclin B1 and other types of cyclins. Here, the question was addressed whether cyclin interaction of pUL97 and additional viral proteins is detectable by mass spectrometry-based approaches. Proteomic data were validated by coimmunoprecipitation (CoIP), Western blot, in vitro kinase and bioinformatic analyses. Our findings suggest that: (i) pUL97 shows differential affinities to human cyclins; (ii) pUL97 inhibitor maribavir (MBV) disrupts the interaction with cyclin B1, but not with other cyclin types; (iii) cyclin H is identified as a new high-affinity interactor of pUL97 in HCMV-infected cells; (iv) even more viral phosphoproteins, including all known substrates of pUL97, are detectable in the cyclin-associated complexes; and (v) a first functional validation of pUL97-cyclin B1 interaction, analyzed by in vitro kinase assay, points to a cyclin-mediated modulation of pUL97 substrate preference. In addition, our bioinformatic analyses suggest individual, cyclin-specific binding interfaces for pUL97-cyclin interaction, which could explain the different strengths of interactions and the selective inhibitory effect of MBV on pUL97-cyclin B1 interaction. Combined, the detection of cyclin-associated proteins in HCMV-infected cells suggests a complex pattern of substrate phosphorylation and a role of cyclins in the fine-modulation of pUL97 activities.
Keywords: CDK ortholog pUL97; Cyclin-associated protein complexes; Human cyclins; Human cytomegalovirus; Molecular modeling; Proteomic analysis

Surface and Extracellular Proteome of the Emerging Pathogen Corynebacterium ulcerans - Bittel, Miriam; Gastiger, Susanne; Amin, Bushra; Hofmann, Jörg; Burkovski, Andreas (Proteomes, 2018)